Non-pharmacological interventions to prevent and manage delirium in critically ill children in neonatal and paediatric intensive care units (NICU/PICU): a scoping review protocol - Zilezinski, Max; Denninger, Natascha-Elisabeth; Tannen, Antje; Kottner, Jan (BMJ open, 2023)
Introduction Delirium is one of the most common forms of acute cerebral dysfunction in critically ill children leading to increased morbidity and mortality. Prevention, identification and management of delirium is an important part of paediatric and neonatological intensive care. This scoping review aims to identify and map evidence on non-pharmacological interventions for paediatric delirium prevention and management in paediatric and neonatal intensive care settings. - Methods and analysis This scoping review will be conducted according to the Joanna Briggs Institute methodology for scoping reviews and reported according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews. Searches will be performed in the databases Medline (via PubMed), CINAHL, Cochrane Library, Ovid (Journals), EMBASE and Web of Science (01/2000-current). Two reviewers will independently review retrieved studies, and relevant information will be extracted using data extraction forms. The results will be presented in tabular format and accompanied by a narrative summary. - Inclusion criteria The review will include references that describe or evaluate non-pharmacological interventions to prevent or manage paediatric delirium. Conference abstracts, editorials, opinion papers and grey literature will be excluded. - Ethics and dissemination Due to the nature of research involving humans or unpublished secondary data, approval of an ethics committee are not required. The dissemination of findings is planned via professional networks and publication in an open-access scientific journal.
Gesehen am 30.01.2024